2020
DOI: 10.1177/0976399620925451
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic Determinants of Temporary Labour Migration in Western Jharkhand, India

Abstract: This article examines the socio-economic determinant of temporary labour migration in Jharkhand. The study uses primary data collected from 12 villages in the western region of Jharkhand. We have used logistic regression model to find out the socio-economic determinant of migration by setting, individual ( n = 4,241) and households ( n = 781). The regression results show that temporary migration is basically from poor households, and migrants are basically male, young and form Scheduled Caste community. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The chances of lower to higher quintile migrants suggest that the highest quintile migrants are less likely to migrate seasonally for a living. Similarly, land keeping is a significant indicator that shows that smaller plots of land appear to migrate more than larger plots of land, which is supported by recent temporary labour migration in Jharkhand (13) . Seasonal migration's spatial patterns reveal an emerging significance phenomenon in the region.…”
Section: Determinant Of Factor Associated With Seasonal Migration In Indiamentioning
confidence: 86%
“…The chances of lower to higher quintile migrants suggest that the highest quintile migrants are less likely to migrate seasonally for a living. Similarly, land keeping is a significant indicator that shows that smaller plots of land appear to migrate more than larger plots of land, which is supported by recent temporary labour migration in Jharkhand (13) . Seasonal migration's spatial patterns reveal an emerging significance phenomenon in the region.…”
Section: Determinant Of Factor Associated With Seasonal Migration In Indiamentioning
confidence: 86%
“…While several studies analyze determinants of temporary migration (Asefawu & Nedessa, 2022;Dodd et al, 2016;Keshri & Bhagat, 2013;Shahriar et al, 2006;Sucharita, 2020), these studies typically consider non-migration as the only alternative. In our study with primary data from rural Bangladesh, we have shown that this standard treatment of temporary migration as a binary choice against non-migration is incomplete in explaining migration decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…A few previous studies examined how such constraining factors influence temporary migration decisions, yielding mixed results (Coffey et al, 2014;Dodd et al, 2016;Konseiga, 2005;Shonchoy, 2015;Sucharita, 2020). These studies mainly compared temporary migration to non-migration.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations